Analysis of wheat value chain: The case of Sinana District, Bale Zone, Oromia Region, Ethiopia - Usman, S. (Haramaya University, 2016)
This study focused on the analysis of wheat value chain in Sinana district of Bale zone with specific objectives of analysing the market structure-conduct-performance of wheat markets; identifying the determinants of wheat supply to the market and market outlet choice of wheat producers, and wheat value addition at different stages of the marketing chain. Primary data were collected from 120 farmers and 37 wheat traders using structured questionnaires. Descriptive statistics and Econometrics models were used to analyze the collected data. Results show that the main wheat value chain actors in the study area are input suppliers, farmers/producers, assemblers, wholesalers, processors, retailers, commission agents and cooperatives. Market concentration ratio at district level was 88.7% which indicated oligopolistic market structure. The result of 2SLS indicated that size of landholding, livestock ownership, family size and quantity of wheat produced influences amount of wheat supplied to market significantly. The multinomial logit model result indicated that the likelihood to choose wholesalers market outlet was significantly influenced by frequency of extension contact, distance from market place, own price of the commodity and membership to cooperative compared to accessing assemblers wheat market outlet. The likelihood of accessing cooperative wheat market outlet was significantly influenced by price given to the commodity and distance from market place compared to accessing assembler market outlet. The likelihood of accessing processors market outlet was significantly influenced by price of commodity, ownership of transportation facilities and distance of processors from production place. Result of probit model indicated that access to market information, quantity of wheat produced, distance from market place access to market information, access to extension and credit services significantly affected farmer’s decision to be engaged in value addition. Therefore, policies aiming at increasing farmer’s awareness of producing value added wheat produce to enhance value creations are recommended to strengthen chain development.